Cranial and Cerebral Anatomic Key Points for Neurosurgery: A New Educational Insight. Issue 1 (January 2022) - Simon, Emile; Beuriat, Pierre-Aurélien; Delabar, Violaine; Jouanneau, Emmanuel; Fernandez-Miranda, Juan; Jacquesson, Timothée
Abstract : BACKGROUND: The anatomy of both the skull and the brain offers many landmarks that could lead surgery. Cranial "craniometric" key points were described many years ago, and then, cerebral key points—along sulci and gyri—were detailed more recently for microneurosurgical approaches that can reach deep structures while sparing the brain. Nonetheless, this anatomic knowledge is progressively competed by new digital devices, such as imaging guidance systems, although they can be misleading. OBJECTIVE: To summarize cranial and sulcal key points and their related anatomic structures to renew their interest in modern neurosurgery and help surgical anatomy teaching. METHODS: After a literature review collecting anatomic key points of skull and brain, specimens were prepared and images were taken to expose skull and brain from lateral, superior, posterior, and oblique views. A high-definition camera was used, and images obtained were modified, superimposing both key points and underlying anatomic structures. RESULTS: From 4 views, 16 cranial key points were depicted: anterior and superior squamous point, precoronal and retrocoronal point, superior sagittal point, intraparietal point, temporoparietal point, preauricular point, nasion, bregma, stephanion, euryon, lambda, asterion, opisthocranion, and inion. These corresponded to underlying cerebral key points and relative brain parts: anterior and posterior sylvian point, superior and inferior rolandic point, supramarginal and angular gyri, parieto-occipital sulcus, and various meeting points between identifiable sulci. Stereoscopic views were also provided to help learning these key points. CONCLUSION: This comprehensive overview of the cranial and sulcal key points could be a useful tool for any neurosurgeon who wants to check her/his surgical route and make the surgery more "gentle, safe, and accurate."